The Effect of Transcutaneous Electrical Nerve Stimulation and Median Nerve Mobilization on Pain Reduction in Carpal Tunnel Syndrome - Sabirin Berampu; Ardianto Saputra; Winda Alfiana; Karnirius Harefa (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Carpal Tunnel Syndrome (CTS) is a peripheral nerve disorder that occurs in the hands and wrists which is characterized by complaints of pain, tingling, numbness and even in severe cases there will be muscle weakness and atrophy of the hand muscles. One of the non-pharmacological or conventional treatments for CTS cases is Transcutaneous Electrical Nerve Stimulation (TENS) and Median Nerve Mobilization. TENS and Median Nerve Mobilization can reduce pain complaints in various neuromuscular cases including CTS. The purpose of the study was to determine the effect of TENS and Median Nerve Mobilization on Pain Reduction in CTS Patients in 2025. Research Methods: type of research was a Quasi Experiment with a Purposive Sampling approach technique. The study population of CTS sufferers was 35 people with a sample size of 15 people. The Action Dose was given 3 times per week for 2 weeks or 6 training sessions. The measuring instrument used was the Visual Analog Scale (VAS). Data Analysis Method: Primary Questionnaire Data was Recapitulated and entered into the SPSS Application and Data Normality Test was carried out with Shapiro-Wilk and Wilcoxon Sign Rank Test with a confidence level of 95%. The results of this study obtained the Normality Value of VAS Pretest with a Significance value of 0.015 and Posttest Significance Value of 0.009 with Interpretation of Non-Normally Distributed Data. And the Results of the Wilcoxon Sign Rank Test obtained a P (Value) of 0.001. And the Average Value of VAS Pretest was 6.4 points, Posttest 2.13 points and the average difference value was 4.27 points. The conclusion of this study is that there is a Difference in the Average Value of Pretest and Posttest Pain After being given TENS and Median Nerve Mobilization Physiotherapy interventions so that it can also be concluded that there is an Effect of Transcutaneous Electrical Nerve Stimulation (TENS) and Median Nerve Mobilization on reducing pain in CTS Patients in 2025.